Moroccan Students’ Attitudes Towards Local and Foreign Languages: The Role of Self-Directed and Language Policy Forces - Bouziane, Abdelmajid (English Studies at NBU, 2020)
Ths article contributes to the hot debate on language preferences and choice at schools and society at large in Morocco from an empirical perspective. It investigates the Moroccan students’ attitudes towards the languages they use in their daily interactions and those that are widely used in the Moroccan education system and attempts to explain whether these attitudes are driven by intrinsic forces or by the language policy orientations set by decision makers. To do so, 1,477 respondents belonging to different school levels and disciplines completed a survey about their frequency of use and mastery of languages, as well as their preferences of language use in the future. Findings show that Moroccan students have positive attitudes towards all languages and would like to use foreign languages for instrumental purposes. They also show that such positive attitudes do not depend on the level of mastery of these languages, nor on their use as mediums of instruction or communication. The findings imply that attitudes towards languages in Morocco are rooted in factors beyond the official policy orientations.